Use of ethnic specific BMI and waist cut-offs for prevention of diabetes and cardiovascular disease - P. Katulanda; R. Jayawardena (Sri Lanka Journal of Diabetes Endocrinology and Metabolism, 2015)
Sri Lanka Journal of Diabetes, Endocrinology and Metabolism 2015; 5: 1-3